2010
DOI: 10.1007/s00417-010-1430-x
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab in combination with laser therapy for the treatment of severe retinopathy of prematurity (ROP) associated with vitreous or retinal hemorrhage

Abstract: In this small series of patients, intravitreal injection of bevacizumab was effective for treatment of severe retinopathy of prematurity associated with vitreous or retinal hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 32 publications
0
34
0
3
Order By: Relevance
“…75,77 Other retinal diseases Several studies reported successful use of bevacizumab in the eyes with severe ROP. 5,78 However, caution is necessary when bevacizumab is used in advanced stages of ROP. Similar to what happens in PDR, the fibrotic component of neovascularization may accelerate after inhibition of angiogenesis and the retinal detachment might worsen.…”
Section: Adverse Events Following Intravitreal Anti-vegf Injections: mentioning
confidence: 99%
See 1 more Smart Citation
“…75,77 Other retinal diseases Several studies reported successful use of bevacizumab in the eyes with severe ROP. 5,78 However, caution is necessary when bevacizumab is used in advanced stages of ROP. Similar to what happens in PDR, the fibrotic component of neovascularization may accelerate after inhibition of angiogenesis and the retinal detachment might worsen.…”
Section: Adverse Events Following Intravitreal Anti-vegf Injections: mentioning
confidence: 99%
“…3 Moreover, promising results were reported with intravitreal injection of anti-VEGF agents for other ocular diseases, such as neovascular glaucoma, 4 retinopathy of prematurity (ROP), 5 and intraocular tumors. 6 Currently, several anti-VEGF drugs, including pegaptanib, ranibizumab, bevacizumab, and aflibercept, are available.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated favorable outcomes after intravitreal anti-VEGF therapy as the first-line treatment, combined or as a salvage therapy after laser for zone-1 disease or APROP [15][16][17][18][19][20][21][22][23][24][25][26]. Despite an ongoing debate about the possible systemic adverse effects, dramatically successful results were encouraging, and IVB monotherapy was considered an option for selected cases [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, its 'off label' intraocular injection is being successfully used for the treatment of different ocular diseases associated with neovascularization. [15][16][17][18][19][20][21] The aim of this study was to evaluate the results of intrasilicone bevacizumab injection at the end of vitrectomy in a series of patients with RRD associated with PVR and to compare the results with those of a control group.…”
Section: Introductionmentioning
confidence: 99%